Business Process Analysis of Outpatient Waiting Time Using Simulation Case Study: Puskesmas ABC (Journal of Business and Management, 2021)
The increased number of visitors and patients visiting public services such as Puskesmas hasbeen a serious concern while the service system stays constant. These unchanged system and growingnumber of patients causing the long waiting problem. Puskesmas ABC's management said that theirflow of patient is slow, especially at Physician’s waiting line. Long waiting time affects patient’ssatisfaction and may cause patient’s illness get worse or transmit their illness to others. The purpose ofthis research is to analyze the quality of the process business, outpatient waiting time, resource allocationin Puskesmas ABC, and the use of a simulation model to analyze outpatient flow, variation of servicetime, and resource utilization. A descriptive study is conducted in order to construct a model thatpossibly used to estimate patient waiting time and service time at the outpatient counter. The waitingtime studied is the queue time starting from the patient registering until being served by a doctoraccording to the standard of waiting time set by the Ministry of Health through the Permenkes onminimum standards of hospital or health services. The data collected by conducting observation andinterview method in Puskesmas ABC. These data are processed and analyzed using Minitab to find thecontrol chart. Furthermore, the collected data examined with various simulations using iGrafx in orderto obtain the most efficient queuing model for proper appointment system. The result of the researchshows that the factors affecting the length of waiting time of the patient are the waiting time atPhysician’s room. Therefore, reducing the workload of medical record staff and improving the flow ofmedical record are able to significantly reduce the waiting time. Furthermore, information andcommunication technology (ICT) tools like online registration and electronic medical records (E-MR)can cut some of the processes and reduce cycle time by a lot.Keywords: Business process, puskesmas, resource utilization, simulation, waiting time